Applications of Ordinary Differential Equations to Problems of Physics and Biology in the Geogebra Program (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article discusses the application of the GeoGebra system of dynamic mathematics for solving ordinary differential equations underlying many physical and biological processes